Awareness and Perception of Students Toward Execution of Internet of Things in Library Services: A study of Indian Institute Technologies of Northern India - Sinha Priyanka; Brar Khushpreet Singh (Open Information Science, 2024)
This study aimed to investigate students’ awareness and perception toward the execution of Internet of Things (IoT) in library services of Indian Institute Technologies (IITs) of Northern India. This study consists of a quantitative research design in which a survey was conducted utilizing a stratified random sampling technique to survey 813 students from five IITs. A total of 780 correctly filled-out surveys were received, yielding a response rate of 95.94%. Statistical tools, including Microsoft Excel and the Statistical Package for the Social Sciences, were used to analyze the data. To assess the significance of the results at the 0.05% level, statistical analysis was carried out utilizing percentages and analysis of variance. This study will communicate the attitude, awareness, and perception of students regarding the implementation of IoT in libraries of IITs. It is conducted to understand the motive behind new technology acceptance in academic libraries. The findings reveal that most of the students got familiar with IoT from browsing on the Web/Internet, social networking sites, research projects, conferences, workshops, webinars and faculty development programs, professional discussions, and meetings, as part of the curriculum. Respondents were in favor of implementing IoT in library services. They believed that IoT will ensure better and more efficient utilization of library resources, followed by real-time information accessibility, recommend IoT-based library services, system content quality will be updated, and will increase the quality of the library; the efficiency of library services will increase with implementation of IoT. It will increase the productivity of library services, be useful in an emergency, and promote information literacy. The study’s findings would be beneficial to libraries and academic institutions interested in implementing IoT applications in their libraries.